“American idiot”: Examining Readers’ Subject Position in One of Green Day’s Albums - Admiral Indra Supardan (Passage, 2013)
This research paper entitled “American Idiot”: Examining Readers’ Subject Position in One of Green Day’s Music Albums is aimed at investigating the ways by which the sixth album of Green Day, American Idiot (2004), ideologically positioned the implied readers in opposite to the USA political agenda. A qualitative descriptive study is employed in this present study. In analyzing the album, which consists of 13 songs, three theoretical frameworks are used: ideological analysis by John Lye (1997), context framework by Adrian Beard (2001), and John Stephens’ (1992) narrative transactions—where he locates the implied readers as the ideological function of a text. By having those frameworks within the analysis, the study discovers five socio-cultural issues, recognized as an attempt to position the implied readers in opposite the US political agenda in Bush administration. These assumptions within the issues known as a subject position are ideologically offered to the readers or the implied readers through narrative aspects; point of view and narrator. Keywords: implied author, implied reader, subject position, ideology, narrative.